In vitro experiments and network pharmacology-based investigation of the molecular mechanism of neferine in the treatment of gastric cancer - Shicong Huang; Yi Nan; Guoqing Chen; Na Ning; Yuhua Du; Shuai Duan; Weiqiang Li; Ling Yuan (PLoS ONE, 2025)
Background Gastric cancer is the world’s leading tumor disease in terms of morbidity and mortality and is currently treated clinically with a comprehensive approach based on surgery. Studies have demonstrated the antitumor effects of neferine, but the anti-cancer mechanism for gastric cancer is not yet clear. Methods The Pubchem and Swiss TargetPrediction databases were searched to retrieve the targets of action of neferine. Meanwhile, relevant gene expression data were downloaded by means of the Gene Expression Omnibus(GEO) database to screen for differential genes and build a drug-disease network. The selected genes were analysed by bioinformatics analysis. Finally, gastric cancer treatment potential of neferine was determined through molecular docking. The molecular mechanism of neferine in the treatment of gastric cancer was verified by CCK8 assay, monoclonal assay, apoptotic and cycle assay, qRT-PCR and Western Blot. Results The results of network pharmacological analyses illustrate that the core genes are closely related to apoptosis, cell cycle, and cell proliferation. Through molecular docking, it was confirmed that neferine were closely related to key proteins. The results of in vitro experiments indicated that neferine could significantly inhibit the viability of gastric cancer cells, induce apoptosis of gastric cancer cells, and block the cell cycle of gastric cancer cells in the G0/G1 phase. Conclusion In summary, neferine inhibited the proliferation of gastric cancer cells through the CDK4/CDK6/CyclinD1 complex. This study provides a theoretical basis for the treatment of gastric cancer with neferine and an idea for the development of neferine for gastric cancer.